Preclinical Studies of PROTACs in Hematological Malignancies - Fuchs, Ota; Bokorova, Radka (Cardiovascular & hematological disorders drug targets, 2021)
Incorrectly expressed or mutated proteins associated with hematologic malignancies have been generally targeted by chemotherapy using small-molecule inhibitors or monoclonal antibodies. But the majority of these intracellular proteins are without active sites and antigens. PROTACs, proteolysis targeting chimeras, are bifunctional molecules designed to polyubiquitinate and degrade specific pathological proteins of interest (POIs) by hijacking the activity of E3-ubiquitin ligases for POI polyubiquitination and subsequent degradation by the proteasome. This strategy utilizes the ubiquitin-proteasome system for the degradation of specific proteins in the cell. In many cases, including hematologic malignancies, inducing protein degradation as a therapeutic strategy offers therapeutic benefits over classical enzyme inhibition connected with resistance to inhibitors. Limitations of small-molecule inhibitors are shown. PROTACs can polyubiquitinate and mark for degradation of "undruggable"proteins, e.g. transcription factor STAT3 and scaffold proteins. Today, this technology is used in preclinical studies in various hematologic malignancies, mainly for targeting drug-resistant bromodomain and extraterminal proteins and Bruton tyrosine kinase. Several mechanisms limiting selectivity and safety of PROTAC molecules function are also discussed.
Keywords: Proteolysis; Humans; lymfom; ubikvitinace; Antineoplastic Agents; zvířata; ubikvitinligasy; leukemie; protinádorové látky; Leukemia; hematologické nádory; Proteasome Endopeptidase Complex; Ubiquitination; Hematologic Neoplasms; proteasomový endopeptidasový komplex; Ubiquitin-Protein Ligases; Animals; lidé; objevování léků; Drug Discovery; proteolýza; Lymphoma